2020
DOI: 10.3390/su12124809
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integrated Approach to Solve Industrial Ground Floor Design Problems

Abstract: The ground floors of buildings usually have high loads from racks and other storage equipment in industrial buildings and logistics centers. Such types of buildings commonly require lift trucks. Therefore, there are special requirements for flatness tolerance across and along the driving track of truck lifts. Structural design solutions must be optimized and sustainable. The article reviews the behavior of soils and the importance of the actual behavior assessment of soils during the design of the ground floor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Investigations have shown that by increasing the thickness of the slab, the difference of the ground slab settlements reduces. Nevertheless, the maximum settlements decrease not significantly (Turskis et al, 2020). Applying such an engineering solution, the amount of concrete will increase significantly as well.…”
Section: Influence Of Support Conditions On the Slab Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations have shown that by increasing the thickness of the slab, the difference of the ground slab settlements reduces. Nevertheless, the maximum settlements decrease not significantly (Turskis et al, 2020). Applying such an engineering solution, the amount of concrete will increase significantly as well.…”
Section: Influence Of Support Conditions On the Slab Behaviourmentioning
confidence: 99%
“…The analysis of the settlements and distribution of bending moments in the modelled fragment "A" has shown that by deepening the piles' foundation and equalizing the stiffness of the subgrade, it is possible not only to achieve the requirements of flatness, but also to reduce the amounts of slab reinforcement. Full-width floor slab settlements calculation (Turskis et al, 2020) tasks were performed using popular structural analysis software, that is based on subgrade reaction theory. Two-parameter theory models were used for the calculations.…”
Section: Numerical Examplementioning
confidence: 99%